The octupole microelectrode for dielectrophoretic trapping of single cells-design and simulation - Ibrahim, Siti Noorjannah; Alkaisi, Maan M. (IEEE Xplore, 2012)

(untitled)
Different microelectrode designs for a dielectrophoresis (DEP)-based lab-on-chip, have significant effect on the DEP force produced. Study on the microelectrode factor is essential, as the geometry and the numbers of microelectrode can influence particles and/or cells polarization. This paper presents one of the three new microelectrode designs, called the octopule microelectrode, in a study on the microelectrode factor of the DEP trapping force. The octupole pattern was constructed on a metal-insulator-metal layer structured on a Silicon Nitride(Si3N4) coated Silicon(Si) substrate. The first layer or back contact is made from a 20nm Nickel-Chromium(NiCr) and a 100nm gold (Au). Then, an insulator made of SU-8-2005 was spin-coated on the metal layer to create arrays of microcavities or cell traps. The third layer, where the octupole geometry was patterned, consists of 20nm NiCr and 100nm Au layers. The microcavities which were defined on the SU-8 layer, allows access to the back contact. Gradient of electric fields which represent the actual DEP trapping regions were profiled using COMSOL Multiphysics 3.5a software. Then, the microelectrode trapping ability was evaluated using polystyrene microbeads suspended in deionised (DI) water as the cell model. Results obtained from the experiment were in agreement with results from simulation studies where polystyrene microbeads concentrated at the trapping region and filled the microcavity.